Non-methane volatile organic compounds emitted from domestic fuels in Delhi: Emission factors and total city-wide emissions. (October 2021) - Mondal, Arnab; Saharan, Ummed Singh; Arya, Rahul; Yadav, Lokesh; Ahlawat, Sakshi; Jangirh, Ritu; Kotnala, Garima; Choudhary, Nikki; Banoo, Rubiya; Rai, Akansha; Yadav, Pooja; Rani, Martina; et al.
Abstract: In controlled laboratory conditions, 62 samples of domestic fuels collected from 56 grids of Delhi were burnt to quantify the emissions of 23 non-methane volatile organic compounds (NMVOCs), i.e., alkanes (11), alkenes (6), alkynes (1) and aromatic compounds (5). The domestic fuels used for residential activities were comprised of 20 unique types of fuel woods, 3 species of crop residue, dung cakes and coal. These fuels are primarily used for cooking and water/space heating during winters. The current study reports the total emission budget of NMVOCs from domestic burning over Delhi. Furthermore, this study also compares the differences in EFs of NMVOCs which are calculated for different burning cycles and sample collection methods. The EFs of NMVOCs calculated from the samples collected during the flaming stage using canisters were analysed for 23 NMVOCs and then compared with same species emitted from complete burning cycle. In addition to this, 10 consumption and emission hotspot grids were also identified in Delhi; based on the ground survey and laboratory simulated results. The total annual usage of domestic fuels for the year 2019 was found to be 0.415 Mt/yr (million tonnes) in Delhi. 12.01 Gg/yr of annual NMVOC emissions was calculated from domestic fuel burning in which the emissions from dung cake and fuel wood dominated with 6.6 Gg/yr and 5.4 Gg/yr, respectively. The EFs of NMVOCs calculated using canister and online collection method differ significantly from each other. The flaming stage presented enhanced emissions compared to the complete burning cycle by 7 times which suggests that the method of data analysis and the period of sample collection play a pivotal role in the preparation of an emission inventory and estimating the budget. Highlights: Emission factor of NMVOC species from domestic fuels Comparison of emission for two different stages of burning City wise emission of NMVOC over Delhi Different hotspots of emission over Delhi, India